Maternal and perinatal characteristics of pregnant women with COVID-19 in a national hospital in Lima, Peru - Huerta Saenz, Igor Hermann (2020)
Introduction: The pandemic of coronavirus disease 2019 (COVID-19) has spread to more than 100 countries. Specific information about its behavior in pregnancy is still limited. Objective: To describe the maternal and perinatal characteristics of pregnant patients infected with COVID-19 and their newborns in a tertiary referral hospital. Methods: Descriptive study. Subjects were all pregnant patients admitted to the OB/GYN Emergency Department of the Edgardo Rebagliati Martins National Hospital from March 24 to May 7, 2020, who were diagnosed with SARS-CoV-2 infection by rapid test or by RT-PCR test. Medical and hospital records were reviewed to retrieve sociodemographic data, patient’s history, clinical manifestations, maternal serology, obstetric complications, delivery mode and perinatal aspects. Results: 41 patients diagnosed with SARS-CoV-2 were identified. 9.2% of all admissions had a positive rapid test. The most common symptoms were cough in 84.6%, fever in 76.9% and sore throat in 61.5%. 68.2% of the patients were asymptomatic, 19.5% had mild illness and 7.3 %, moderate. 2 cases progressed to severe pneumonia requiring non-invasive ventilation. No maternal deaths were recorded. 21.7% were vaginal deliveries, while 78.3% were C-sections. One baby born in a vaginal delivery had a positive PCR result on day 8. Conclusions: A large percentage of asymptomatic pregnant patients had a positive PCR test. Implementing universal screening among patients in labor as part of the pregnant patient flow protocol is necessary for all institutions.